Creation of transgenic Brassica napus L. plants expressing human alpha 2b interferon gene - Sakhno, L.O.; Kvasko, O.Y.; Olevinska, Z.M.; Spivak, M.Y.; Kuchuk, M.V. (Цитология и генетика, 2012)
Spring rapeseed transgenic lines expressing human interferon alpha 2b were created by Agrobacteriummediated transformation of aseptic plant leaf explants. The maximum antiviral activity of the leaf extracts reached 4500 IU/g fresh weight. It was determined that the antioxidant activity and the activity of an enzyme of plant antioxidant system – superoxide dismutase (SOD) – in the leaf tissues of transgenic plants increased compared to controls. There were no correlations between the interferon and antioxidant activities, as well as between SOD and interferon activities. Using the obtained transgenic rapeseed plants with high interferon and antioxidant activities as a feed additive for animals might have preventive effect on their body, increasing resistance to infections of various origins. Методом агробактериальной трансформации листовых эксплантов асептических растений ярового рапса получены линии, экспрессирующие альфа 2b интерферон человека. Максимальная противо-вирусная активность экстрактов листьев достигала 4500 МЕ/сырого веса. Установлено, что антиоксидантная активность и активность одного из ферментов антиоксидантной системы растений – супероксиддисмутазы (СОД) – в тканях листьев трансгенных растений повышена по сравнению с контрольными. Не выявлено корреляции как между активностью интерферона и антиоксидантной активностью, так и между активностью интерферона и активностью СОД. Использование полученных трансгенных растений рапса с высокой активностью интерферона и повышенной антиоксидантной активностью как добавки к кормам животных могло бы оказывать профилактическое влияние на их организм, повышая устойчивость к различным инфекциям. Методом агробактеріальної трансформації листових експлантів асептичних рослин ярого ріпака отримано лінії, що експресують альфа 2b інтерферон людини. Максимальна противірусна активність екстрактів листків сягала 4500 МО/сирої ваги. Встановлено, що антиоксидантна активність і активність одного з ферментів антиоксидантної системи рослин – супероксиддисмутази (СОД) – в тканинах листків трансгенних рослин підвищена в порівнянні з контрольними. Не виявлено кореляції ні між активністю інтерферона і антиоксидантною активністю, ні між активністю інтерферона і активністю СОД. Використання отриманих трансгенних рослин ріпака з високою активністю інтерферона та підвищеною антиоксидантною активністю як добавки до кормів тварин мало б профілактично впливати на їхній організм, підвищуючи стійкість до інфекцій різного походження.